Keahlian Retorika pada Mahasiswa Bimbingan dan Konseling Universitas Mathla’ul Anwar Banten - Ikhsan, Muhamad (Jurnal Artikula, 2023)
Rhetoric is the art of face-to-face verbal communication from an individual to a general audience. Studying the art of rhetoric has many advantages, so students need to master this speaking technique. The research method uses qualitative methods with interview data collection techniques for guidance and counseling students at Mathla'ul Anwar University (UNMA) Banten. Rhetoric is one of the skills that students must learn, including guidance and counseling students who will have a lot of contact with other people as counselors or guidance counselors at school. Research results show that rhetoric is an important part of lectures. In the future, studying rhetoric will be very beneficial. These skills will become soft skills that are taken into account both in the university environment and in the work environment. When someone has a good way of communicating, they will have their own charm and be respected by other people. Researchers limit the problem studied in this paper to the benefits gained from studying rhetoric for the future.